Up-close for solo cello, string ensemble and film - Aa, Michel van der 1970- (Disquiet Media, 2011)
"Part cello concerto, part film opera, Michel van der Aa's Up-close explores the human condition through reflected and overlapping sounds, images and plotlines. The actions of the woman and the cellist come closer and closer until at the end they mimic one another, without ever completely connecting. Images and music leak from screen to stage and back again in a poetic exploration of the rituals of communication"--Container
Musical work for solo violoncello, string orchestra, film and soundtrack
Interpreten: Sol Gabetta, violoncello. Vakil Eelman, actress (on film inserts). Amsterdam Sinfonietta
Aufnahme: Amsterdam Muziekgebouw aan 't IJ, 15 März 2011
Director of photography, Joost Rietdijk ; lighting design, Jurgen Kolb ; gaffer, lighting design, Wietse Vos ; video editor, Michel van der Aa ; executive producer, Joggem Simons
Credits for film inserts that form part of the performance: Michel van der Aa, director & script ; Joost Rietdijk, director of photography ; Wietze Vos, light design
Keywords: Cello with string orchestra; Concertos (Cello with string orchestra); Mixed media (Music); Music theater; Filmed operas; Filmed performances; Nonfiction films; DVD-Video